Iklan Audio Sprite versi Bercocok Tanam dan Persepsi Penyandang Disabilitas Netra - Wijaya, Evan Timothy; Sukendro, Gregorius Genep (Fakultas Ilmu Komunikasi Universitas Tarumanagara, 2023)
Advertising is a form of communication in which the recipient receives stimulation from the advertisement, the perception of persons with visual disabilities towards an advertisement is influenced by the interpretation of the